Immature Granulocytes: A Risk Factor of Infection after Cardiac Surgery. Issue 6 (16th October 2018) - Daix, Thomas; Guérin, Estelle; Tavernier, Elsa; Marsaud, Jean‐Philippe; Hacan, Adélaïde; Gauthier, François; Piccardo, Alessandro; Vignon, Philippe; Feuillard, Jean; François, Bruno
Abstract : Background: Similarly, to sepsis, cardiac surgery with cardiopulmonary bypass (CPB) induces major changes in leukocyte subsets. Immature granulocytes (IGs) increase both in sepsis and after open‐heart surgery. Secondary infections are a major complication of cardiac surgery with CPB. We hypothesized that the assessment of leukocyte subsets with multicolor flow cytometry (FCM) could help the front‐line clinician to better identify patients at high risk of infectious complications in this clinical setting. Methods: In this single‐center observational pilot study, we identified 26 leukocyte subsets using three combinations of antibodies (from 5 to 10 colors per combinations): one devoted to granulocytes, one to lymphocyte subpopulations and one for rare cells (plasma cells and dendritic cells). Blood samples were obtained preoperatively and immediately after open‐heart surgery under CPB in 59 patients without immuno‐depression, chronic or neoplastic inflammatory disease, and immunosuppressive treatment. Secondary infections during hospital stay were recorded. Results: Patients exhibited postoperative NK and T‐cell lymphopenia, increased levels of IGs and monocytes with low levels of surface HLA DR. Twelve patients developed secondary infectious complications. Only immediate postoperative IG levels were significantly higher in these patient (6.6 [6; 7.39] G/L vs. 3.8 [2.67; 5.72] G/L, P = 0.01). Patients with immediate postoperative increase of IGs developed more frequently infectious complication (10/22 [46%] vs. 2/37 [5%]: P < 0.001). Conclusions: This study suggests that postoperative increase of IGs is related to postoperative organ failure and promises to help in early identification of patients at risk of infectious complications after open‐heart surgery under CPB. © 2018 International Clinical Cytometry Society